2009
DOI: 10.1371/journal.ppat.1000435
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Thermal Sensing Controls Proteolysis of Yersinia Virulence Regulator RovA

Abstract: Pathogens, which alternate between environmental reservoirs and a mammalian host, frequently use thermal sensing devices to adjust virulence gene expression. Here, we identify the Yersinia virulence regulator RovA as a protein thermometer. Thermal shifts encountered upon host entry lead to a reversible conformational change of the autoactivator, which reduces its DNA-binding functions and renders it more susceptible for proteolysis. Cooperative binding of RovA to its target promoters is significantly reduced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
100
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 53 publications
0
100
0
Order By: Relevance
“…Y. pseudotuberculosis is a foodborne pathogen closely related to Y. pestis and causes enteritis, diarrhea, and mesenteric lymphadenitis in animals and humans. Its metabolism and virulence are strictly temperature controlled by various posttranscriptional mechanisms (6,26). An intercistronic RNAT is present upstream of low calcium response gene F (lcrF) coding for the master regulator of Yersinia virulence (6).…”
mentioning
confidence: 99%
“…Y. pseudotuberculosis is a foodborne pathogen closely related to Y. pestis and causes enteritis, diarrhea, and mesenteric lymphadenitis in animals and humans. Its metabolism and virulence are strictly temperature controlled by various posttranscriptional mechanisms (6,26). An intercistronic RNAT is present upstream of low calcium response gene F (lcrF) coding for the master regulator of Yersinia virulence (6).…”
mentioning
confidence: 99%
“…Moreover, significantly higher amounts of RovA were identified in YeO:3 strains at 25°C and 37°C. This result was unexpected, as it was recently shown that RovA synthesis of Y. pseudotuberculosis is positively autoregulated and subjected to temperature regulation on the post-transcriptional level (Herbst et al, 2009). RovA acts as an intrinsic thermometer.…”
Section: Role Of Rova For Virulence Of Yeo:3mentioning
confidence: 96%
“…upon uptake by the human host) induces reversible conformational changes. These alterations reduce the DNA-binding capacity of RovA and render the regulator more susceptible to proteolysis by the Lon protease (Herbst et al, 2009). As a consequence, RovA of Y. pseudotuberculosis is rapidly degraded at 37°C and less able to induce its own transcription due to a lower DNA binding ability.…”
Section: Role Of Rova For Virulence Of Yeo:3mentioning
confidence: 99%
“…Temperature represents a major stimulus for Yersinia to adjust metabolism and virulence gene expression, indicating that besides proteineaceous thermosensors such as the virulence regulator RovA [41], RNATs also represent reasonable players in this process. Surprisingly, so far only one RNAT has been identified and characterized in Y. pseudotuberculosis, the lcrF RNAT located in the intergenic region of the yscWlcrF operon [42] [44].…”
Section: Rna Thermometers (Rnats)mentioning
confidence: 99%